Influence of Watching Professional Baseball on Japanese Elders' Affect and Subjective Happiness. (13th July 2017) - Kawakami, Ryoko; Sawada, Susumu S.; Ito, Tomoko; Gando, Yuko; Fukushi, Tomohiro; Fujie, Ryosuke; Oka, Koichiro; Sakamoto, Shizuo; Higuchi, Mitsuru
Objective: To determine the effects of watching a professional baseball game on the affect and subjective happiness of elders without a specific team to support.Method: Elderly Japanese ( n = 16) were instructed to watch baseball games at a ballpark. They answered a questionnaire several weeks before (baseline) and, on the day of the game, before and after watching the game. Participants' affect and happiness were assessed using the General Affect Scale and Subjective Happiness Scale, respectively.Results: Calmness had a tendency to increase from baseline to before watching the game ( p = .052). Furthermore, subjective happiness significantly increased after watching the game, compared with baseline ( p = .017).Discussion: Visiting a ballpark to watch a professional baseball game increased elders' subjective happiness after they had finished watching it.